Early Effects of Ionizing Radiation on the Collagen Hierarchical Structure of Bladder and Rectum Visualized by Atomic Force Microscopy. (27th February 2018) - Kotova, Svetlana L.; Timashev, Peter S.; Belkova, Galina V.; Kochueva, Marina V.; Babak, Ksenia V.; Timofeeva, Victoria A.; Kiseleva, Elena B.; Vasilieva, Olga O.; Maslennikova, Anna V.; Solovieva, Anna B.
Abstract: Radiation therapy, widely used in the treatment of a variety of malignancies in the pelvic area, is associated with inevitable damage to the surrounding healthy tissues. We have applied atomic force microscopy (AFM) to track the early damaging effects of ionizing radiation on the collagen structures in the experimental animals' bladder and rectum. The first signs of the low-dose radiation (2 Gy) effect were detected by AFM as early as 1 week postirradiation. The observed changes were consistent with initial radiation destruction of the protein matrix. The alterations in the collagen fibers' packing 1 month postirradiation were indicative of the onset of fibrotic processes. The destructive effect of higher radiation doses was probed 1 day posttreatment. The severity of the radiation damage was proportional to the dose, from relatively minor changes in the collagen packing at 8 Gy to the growing collagen matrix destruction at higher doses and complete three-dimensional collagen network restructuring towards fibrotic-type architecture at the dose of 22 Gy. The AFM study appeared superior to the optical microscopy-based studies in its sensitivity to early radiation damage of tissues, providing valuable additional information on the onset and development of the collagen matrix destruction and remodeling.